The asymmetric response of travel demand to twitter-based uncertainty: A global empirical assessment. (March 2023) - Cobanoglu, Cihan; Kocak, Emrah
Abstract: This paper examines the impact of two new Twitter-based uncertainty metrics on global travel demand, using linear and non-linear methods with daily data for the period 15 December 2020 and 20 March 2022. According to the linear results, an increase (decrease) in Twitter-based uncertainty affects travel demand negatively (positively). However, nonlinear estimations show that the relationship is asymmetrical, not symmetrical. Accordingly, travel demand is responding to the Twitter-based increase in uncertainty but is unaffected by reductions in uncertainty. Finally, it is pointed out that there may be asymmetries between tourism and uncertainty for future research.